In Silico Analysis of the Antidepressant Fluoxetine and Related Drugs at SARS-CoV-2 Main Protease (Mpro) and Papain-like Protease (PLpro) - Tronco Pauletto, Pedro José; Omage, Folorunsho B.; Delgado, Cássia Pereira; Nogara, Pablo Andrei; Teixeira Rocha, João Batista (Current Drug Discovery Technologies, 2023)
Background: SARS-CoV-2 main protease (Mpro or 3CLpro) and papain-like protease (PLpro) are common viral targets for repurposed drugs to combat COVID-19 disease. Recently, several antidepressants (such as fluoxetine, venlafaxine and citalopram) belonging to the Selective Serotonin Reuptake Inhibitors (SSRIs) and the Serotonin-Norepinephrine Reuptake Inhibitors (SNRI) classes have been shown to in vitro inhibit viral replication. Aim: Investigate a possible action of fluoxetine and derivatives on SARS-CoV-2 protease sites. Methods: Molecular docking was performed using AutoDock Vina. Both protease structures and different drug conformations were used to explore the possibility of SARS-CoV-2 inhibition on a Mpro or PLpro related pathway. Drug structures were obtained by optimization with the Avogadro software and MOPAC using the PM6 method. Results were analysed on Discovery Studio Visualizer. Results: The results indicated that Mpro interacted in a thermodynamically favorable way with fluoxetine, venlafaxine, citalopram, atomoxetine, nisoxetine and norfluoxetine in the region of the active site, whether PLpro conformers did not come close to the active site. Conclusion: In an in silico perspective, it is likely that the SSRIs and other anti-depressants could interact with Mpro and cause the enzyme to malfunction. Unfortunately, the same drugs did not present similar results on PLpro crystal, therefore, no inhibition is expected in an in vitro trial. Anyway, in vitro tests are necessary for a better understanding of the links between SARS-CoV-2 proteases and antidepressants.
Keywords: PLpro